Who will be the mediator? Local politics and hospital closures in Germany - Ieva Sriubaite (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
This paper analyses the effects of hospital closures in Germany in the context of emergency medical care for patients with acute myocardial infarction or hemorrhagic stroke. Using a comprehensive inpatient care data, I evaluate the extent of the impact of hospital closures between 2006 and 2012 on geographical healthcare access and several patient clinical outcomes. To minimize bias from the potential endogeneity between the hospital quality and market structure, I employ an instrumental variable strategy and build a strong and highly relevant instrument in the context of municipal politics. Using collected data on the turnout of each local election in Germany, I compute a measure of concentration in political power that is estimated by the winning margin of the largest centre-right political party in Germany against the opposition. My findings suggest that: first, while patients living in closure-affected areas face worse healthcare access, this does not result in lower survival for acute medical cases; second, that a hospital closure mainly affects the access for rural residents and stimulates the efficiency of hospitals located in the more densely populated areas; and political power in the area plays an important role in shaping hospital's future in the local market. – – Dieser Beitrag analysiert die Auswirkungen von Krankenhausschließungen in Deutschland im Kontext der notfallmedizinischen Versorgung von Patienten mit akutem Myokardinfarkt oder hämorrhagischem Schlaganfall. Unter Verwendung umfassender Daten zur stationären Versorgung evaluiere ich das Ausmaß der Auswirkungen von Krankenhausschließungen zwischen 2006 und 2012 auf den Zugang zur Gesundheitsversorgung und verschiedene klinische Ergebnisse der Patienten. Um Verzerrungen durch die potentielle Endogenität zwischen der Krankenhausqualität und der Marktstruktur zu minimieren, verwende ich einen Instrumentenvariablenansatz. Meine Ergebnisse legen nahe, dass erstens Patienten, die in von Schließungen betroffenen Gebieten leben zwar einen schlechteren Zugang zur Gesundheitsversorgung haben, dies führt aber nicht zu einer geringeren Überlebensrate bei akuten medizinischen Fällen; zweitens, dass die Schließung eines Krankenhauses vor allem den Zugang für Bewohner ländlicher Gebiete betrifft und die Effizienz von Krankenhäusern erhöht, die sich in den dichter besiedelten Gebieten befinden; und drittens die politische Macht in der Gegend eine wichtige Rolle für die Zukunft des Krankenhauses auf dem lokalen Markt spielt.
Keywords: I11; I15; I18; I19; 330; Hospital closure; quality of care; municipality election; instrumental variablee